2011
DOI: 10.1158/0008-5472.can-10-4633
|View full text |Cite
|
Sign up to set email alerts
|

18F-Fluorodeoxy-glucose Positron Emission Tomography Marks MYC-Overexpressing Human Basal-Like Breast Cancers

Abstract: In contrast to normal cells, cancer cells avidly take up glucose and metabolize it to lactate even when oxygen is abundant, a phenomenon referred to as the Warburg effect. This fundamental alteration in glucose metabolism in cancer cells enables their specific detection by Positron Emission Tomography (PET) following intravenous injection of the glucose analogue 18F-fluorodeoxy-glucose (18FDG). However, this useful imaging technique is limited by the fact that not all cancers avidly take up FDG. To identify mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
110
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(119 citation statements)
references
References 54 publications
(62 reference statements)
9
110
0
Order By: Relevance
“…8 studies used data from The Cancer Genome Atlas (TCGA) and/or The Cancer Imaging Archive (TCIA); 1,16,23,27,32,34,38,41 2 studies were multi-institutional; 9,19 and the remaining 17 studies used local institutional data. 15,17,18,[20][21][22][24][25][26]28,30,31,33,[35][36][37]39,40 26 out of 27 studies were retrospective in design. The number of patients ranged from 10 to 104 patients, with a median of 38 patients.…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
See 1 more Smart Citation
“…8 studies used data from The Cancer Genome Atlas (TCGA) and/or The Cancer Imaging Archive (TCIA); 1,16,23,27,32,34,38,41 2 studies were multi-institutional; 9,19 and the remaining 17 studies used local institutional data. 15,17,18,[20][21][22][24][25][26]28,30,31,33,[35][36][37]39,40 26 out of 27 studies were retrospective in design. The number of patients ranged from 10 to 104 patients, with a median of 38 patients.…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
“…8 (30%) studies used a validation data set to verify the association between imaging features and genomic data identified in the initial data set. 20,22,23,27,28,34,37,40 Six types of cancers were studied: glioblastoma multiforme (GBM)/high-grade glioma (n 5 14, 52%), non-small-cell lung cancer (NSCLC) (n 5 3, 11%), hepatocellular carcinoma (HCC) (n 5 3, 11%), breast cancer (n 5 5, 19%), clear-cell renal cell carcinoma (CCRCC) (n 5 1, 4%) and cervical cancer (n 5 1, 4%). The imaging modalities used included fluorine 18 fludeoxyglucose positron emission tomography (PET) (n 5 4, 15%), MRI [n 5 18 (including two perfusion MR), 67%] and CT [n 5 5 (including one perfusion CT), 19%].…”
Section: Published Studies Using a Radiogenomic Approach In Cancer Rementioning
confidence: 99%
“…), thus it will be of interest to determine whether this regulatory mechanism correlates exclusively with MYC status or whether other regulators also contribute. Triple negative breast cancers have high MYC levels, high rates of aerobic glycolysis, a glycolytic gene signature, and express glutaminase (Chandriani et al 2009;Foulkes et al 2010;Palaskas et al 2011;Horiuchi et al 2012). Consistent with these findings, triple negative breast cancers are more dependent on glutamine for growth than luminal cancers (Kung et al 2011).…”
Section: Interactions Between Nutrient Utilization and Nutrient Availmentioning
confidence: 54%
“…This rationale has been explored in research but no attempt to investigate a clinical application has been initiated. A small amount of work has already been initiated looking more specifically at radiogenomics/radioproteomics in tumors [2][3][4][5][6][7][8][9], as well as prognosis and therapy modulation. Fukuda et al showed a significant negative correlation between the metabolic rate of oxygen and Fluorodeoxyglucose (FDG) standardized uptake value (SUV) in human liver tumors [10].…”
mentioning
confidence: 99%
“…Dooms et al on the other hand found that the percentage of viable tumor cells and Ki-67 length density after induction chemotherapy were significantly lower in metabolic responders compared with non-responders [11]. Palsakas et al identified an "FDG signature" in the basal subtype of breast cancer and correlated that with the over expression of the transcription factor c-MYC [9]. His group identified a higher FDG score for this subtype of breast cancer.…”
mentioning
confidence: 99%